2017
DOI: 10.22202/bc.2017.v3i1.2726
|View full text |Cite
|
Sign up to set email alerts
|

Etnofarmakologi Tumbuhan Familia Rhizophoraceae oleh Masyarakat di Indonesia

Abstract: Etnofarmakologi adalah studi yang menggunakan tumbuhan sebagai obat oleh orang-orang yang mendiami wilayah tertentu. Beberapa orang di Indonesia masih menggunakan jamu sebagai obat tradisional, serta masyarakat yang tinggal di sekitar hutan bakau. Salah satunya adalah Rhizophoraceae, tanaman ini umumnya merupakan konstituen utama tanaman mangrove. Penelitian ini bertujuan untuk mengetahui pemanfaatan relatif Rhizophoraceae sebagai tanaman obat di hutan mangrove. Hasil penelitian ini, ada tiga spesies dari fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…Studies including ethnographic research on traditional medicine, in vitro research, in vivo research using various cells and experimental animals reported Rhizophora apiculata extract as potential medicine. [1,[3][4][5] This extract has antioxidant, anti-inflammatory, antitumor, and certain effects. [5-7,11] However, it is necessary to study the possible side effects caused by the consumption of this extract by humans to be developed as a medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies including ethnographic research on traditional medicine, in vitro research, in vivo research using various cells and experimental animals reported Rhizophora apiculata extract as potential medicine. [1,[3][4][5] This extract has antioxidant, anti-inflammatory, antitumor, and certain effects. [5-7,11] However, it is necessary to study the possible side effects caused by the consumption of this extract by humans to be developed as a medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Fruits, flowers, and leaves of the plant are used by some Indonesian for traditional medicine especially for treating heartburn and stomach aches. [1] Furthermore, it was also utilized for treating nausea, vomiting, diarrhea, and amoebiasis in India. [2] Previous studies indicated that the bark extract of Rhizophora apiculate performed as antioxidant activities and anti-inflammatory effects.…”
Section: Rhizophoramentioning
confidence: 99%
“…They were traditionally used by some Indonesian people to treat stomach aches and heartburn by drinking boiled water from their leaves, flowers, and fruits. [5] Moreover, traditional healer in India used it to treat diarrhea, amoebiasis, vomiting, and nausea. [6] Cigarette smoke is a common source of reactive oxygen species (ROS), which is proven to be associated with decreased male fertility and poor semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…They were traditionally used by some Indonesian people to treat stomach aches and heartburn by drinking boiled water from their leaves, flowers, and fruits. [5] Moreover, traditional healer in India used it to treat diarrhea, amoebiasis, vomiting, and nausea. [6] It was reported that the bark extract of R. apiculata showed antioxidant activities.…”
Section: Associatedmentioning
confidence: 99%
“…Di kota Pariaman masyarakat telah memanfaatkan 10 species tumbuhan magrove sebagai obat-obatan (Leilani, Rizki, Sari, Sari, 2017). Pemanfaatan tumbuhan sebagai obat ini tidak hanya pada tumbuhan teresterial saja, namun tumbuhan-tumbuhan yang hidup di perairan, seperti tumbuhan familia Rhizophoraceae yang tumbuh di hutan mangove di Teluk Buo Padang yang dimanfaatkan sebagai tumbuhan obat (Rizki, & Leilani, 2018), begitu juga di hutan mangrove yang terdapat di kota Pariaman (Milda, Leilani, & Rizki, 2012). salah satu daerah di Padang Pariaman yang masih memanfaatkan tumbuhan sebagai obat adalah jorong Indarung kenagarian Aia Tajun kecamatan Lubuk Alung Kabupaten Padang Pariaman.…”
Section: Pendahuluanunclassified